Caregiver drug use in Ontario child welfare investigations: The need for coordinated intervention. (November 2021) - Joh-Carnella, Nicolette; Fallon, Barbara; Lefebvre, Rachael; Lindberg, Daniel; Davidson, Laura
Abstract: Background: Caregiver substance abuse is associated with harmful parenting behaviors, increased child welfare involvement, and negative child outcomes, and the opioid epidemic has brought increased attention to the safety and wellbeing of children living with caregivers who abuse substances. Objective: This paper investigates the impact of primary caregiver drug abuse concerns on child welfare investigations in Ontario, Canada and examines how different drug abuse categories impact out-of-home placements in a Canadian setting, with a focus on opioids, opiates, and morphine derivatives. Participants and setting: Secondary analyses of data from the Ontario Incidence Study of Reported Child Abuse and Neglect 2018 (OIS-2018) were conducted. The OIS-2018 collected information on child welfare investigations from workers who conducted the investigations. The final unweighted sample of the OIS-2018 included 7590 investigations involving children under 18 years old. Methods: Descriptive and bivariate analyses were conducted as well as a logistic regression predicting out-of-home placement. Results: Investigations involving noted primary caregiver drug abuse concerns involved increased household and family risks as well as more intrusive forms of child welfare involvement. Results of the logistic regression controlling for family, child, and case characteristics revealed that investigations involving noted primary caregiver drug abuse were more likely to involve out-of-home placements, and investigations that involved caregivers who abused opioids specifically were approximately 3.5 times more likely to result in a placement. Conclusions: A coordinated response involving the child welfare, addictions treatment, and other allied systems is warranted to support families with substance abuse concerns and provide appropriate services.